THE CHARACTERISTICS OF WAR CRIMES UNDER INTERNATIONAL LAW: A Case Study of the Russia and Ukraine War - Raharja, Yolanda Damai; Widoyoko, Wreda Danang (jfpublisher, 2023)
War is a physical or non-physical act of fighting over something that is important to the war participants. War crimes are violations of International Law. Therefore, there are several rules to deal with war crimes in international law as regulated in International Humanitarian Law, which has various scopes in the regulation, such as the Geneva Convention, The Hague Convention, and jurisprudence agreements and there is a existing provision or regulation to combat crimes that are considered a serious threat to humanity for crimes that occur with the need for a rule, that is International Criminal Law. In November 2013, during the Maidan protests in Ukraine, which led to the removal of the pro-Russian former president Viktor Yanukovich and the beginning of conflict over Russia’s invasion of Ukraine. The objective of this research is to determine and analyze the types of International Law violations during the war between Russia and Ukraine. The method used is the normative juridical method combined with a statutory approach to analyze relevant international legal instruments and a factual approach related to the events that occurred in the invasion. The research results indicate that war crimes are criminal offenses in international law that are more specifically regulated in International Humanitarian Law. However, regarding this war crimes, data and facts based on thorough and independent investigations have not been found, but only from media information that is doubtful, so that the existence of war crimes cannot be confirmed.